Fibre types of M. pectineus of the cat (Felis domestica). - Rodrigues, A. C. [UNESP]; Dall Pai, V. [UNESP]; Tamega, O. J. [UNESP]; Guazzelli Filho, J. [UNESP] (My University, 1990)
As revealed by the NADH-diaphorase, SDH and myosin ATPase, the M. pectineus of the cat possesses at least 3 main kind of fibres, with different distribution on the superficial and deep portions of the muscle. The superficial portion revealed that 23.6% are FOG fibres: 17.8% are SO fibres and 58.6% are FG fibres. Already the deep portion revealed that 61.4% are FOG fibres: 14.5% are SO fibres and 24.1% are FG fibres. The myosin ATPase reaction was used to demonstrate contracting characteristics. These findings suggest that the movements of fast contraction of M. pectineus are predominant.